Estado digital: Dados e políticas públicas no Brasil - Denise do Carmo Direito; Valéria Luzia Mota Barros (Instituto de Pesquisa Econômica Aplicada (IPEA), 2025)
– This text aims to address the following question: What are the main debates related to data when considering public action in the Brazilian literature? To answer this question, a narrative literature review was conducted, focusing on studies that examine the relationship between data and governance, specifically in the context of Brazil and published from 2019 onward. The analysis reveals two central issues. The first concerns the importance of data in the public sector, its role in enhancing public policies, as well as the role of the State as both a producer and analyzer of data. The second issue revolves around open government and the use and reuse of public data across public and private sectors. The period examined - from 2019 to the present - is marked by two significant events that are prominent in texts from this time: the enactment of the General Data Protection Law (2018) and the Covid-19 pandemic. In conclusion, some of the priorities highlighted by this literature are problematized and critically examined, with an assessment that the debate on data is somewhat underdeveloped, considering the fields of public administration and public action.
Keywords: D73; H83; P55; 330; data and public action; open government; data protection; inter-federative and intersectoral coordination